DESCRIPTIVE ANALYSIS OF BURNOUT SYNDROME IN PROFESSIONAL DENTAL STUDENTS OF DENTAL FACULTY, SULTAN AGUNG ISLAMIC UNIVERSITY, SEMARANG - Kusuma Arbianti; Moh. Husnun Niam; lqlima Mindaniati (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Professional education is carried out in a community with various forms and genuine services. A large number of demands on academic assignments and practical assignments that cause stress to students of the dental profession continuously will lead to a state of work fatigue or burnout syndrome, which is divided into three dimensions: emotional exhaustion, depersonalization, and decreased self-performance. This study aims to analyze the occurrence of burnout syndrome based on the dimensions of emotional exhaustion, depersonalization, and reduced self-performance.MethodS: This type of research uses an observational and cross-sectional approach. The sampling technique with simple total sampling obtained 168 respondents. Data collection was carried out by giving a questionnaire regarding burnout syndrome. Statistical analysis used a univariate analysis test and was described descriptively.ResultS: Test results on the dimensions of emotional exhaustion in the heavy category are 72.2%, in the medium category 25%, and in the mild category 2.8%.Conclusion: The results of the depersonalization dimension test were 13% in the severe category, 29.9% in the medium category, and 61.1% in the mild category. The test results for the dimensions of low personal accomplishment in the heavy category were 73.1%, in the medium category 22.2%, and the mild category 4.6%.